Reliability of the Weather Radar at BBMKG Region III Using the Failure Mode and Effect Analysis (FMEA) Method - Ferary, Franky; Gunantara, Nyoman; Pramaita, Nyoman (Department of Electrical Engineering, Faculty of Engineering, Universitas Negeri Surabaya, 2025)
One of the main roles of BMKG in Serving the public is to provide weather forecast information. The accuracy of such information highly depends on the operational condition of the instruments used, including weather radar as one of the primary tools. A reliable weather radar ensures the generation of accurate observational data, which forms the basis of weather forecasting. This study aims to assess the reliability of the weather radar operated by BBMKG Region III Badung, which has been in service for over 15 years. The evaluations were conducted using the Failure Mode and Effect Analysis (FMEA) method based on the latest calibration data from 2024. The analysis revealed several significant potential failures, particularly in the receiver component, with Risk Priority Number (RPN) values exceeding 100. These findings indicate a high level of risk that could affect the radar’s sensitivity in detecting rainfall. Nevertheless, the weather radar at BBMKG Region III remains capable of identifying rainfall intensity ranging from light to very heavy. Keywords: Weather radar, BMKG, Reliability, FMEA, Receiver, Rainfall intensity